The impact of values on the motivation of domestic tourists in Saudi Arabia - Alsaeed, Turki Saad (2013)
Saudi Arabia is the world's leading oil producer and exporter. The economy in the country is almost totally dependent on oil. Tourism is one of the sectors which received more attention in the last few years after the establishment of the Saudi Commission for Tourism and Antiques in 2000. The Commission's main purpose is to develop, promote and enhance the tourism sector, particularly the domestic tourism sector, to be one of the important sectors in economy. The main purpose of this research is to identify motivations and values for Saudi citizens to travel domestically. Maslow's Motives Modal (1998) and Rokeach Value Survey (1973) are applied in the study. Motivations are examined by understanding the 'push' and 'pull' factors and these concepts have been used in many studies. The idea behind these concepts is that people travel because they are pushed by their own internal forces and pulled by external forces of the destination attributes. The study was conducted in five regions in Saudi Arabia and 308 questionnaires were obtained, 86 from central region, 46 from western region, 37 from eastern region, 50 from northern region and 89 from southern region. Obtained data were analyzed using SPSS. The findings indicated that there are five push motivations for Saudi domestic tourists including (Relaxation, Escape, Knowledge, Family and Cultural) and seven pull factors including (Religious, Safety, Spirituality, Economicl, Entertainment, Shopping and Local culture). The study showed that the push factor of Relaxation and the pull factor of Religion are the most important factors as perceived by Saudis. The study suggested further research to be carried out across the Muslim and Arab world in order to explore more travel motivations and values dimensions for people in this region.